2020
DOI: 10.14740/jocmr4335
|View full text |Cite
|
Sign up to set email alerts
|

A Coronary Artery Calcium Score of Zero in Patients Who Have Undergone Coronary Computed Tomography Angiography Is Associated With Freedom From Major Adverse Cardiovascular Events

Abstract: Background: The coronary artery calcification score (CACS) is a good marker of future cardiovascular risk. We determined the association between the CACS and the prognosis in patients who have undergone coronary computed tomography angiography (CCTA). Methods: We performed a prospective cohort study and enrolled 502 consecutive patients who underwent CCTA for screening of coronary artery disease (CAD) at Fukuoka University Hospital (FU-CCTA Registry) and either were clinically suspected of having CAD or had at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…MACE rates in stable chest pain patients with CCS 0 were reported in 19 studies ( Supplementary Table 3 ). CCS 0 was present in 27–100 % of the included cohorts 12 13 14 15 18 19 28 38 39 40 41 42 43 44 45 46 47 48 . Of the CCS 0 patients, 0–2.1 % suffered from MACE during a follow-up period from 1.6 to 6.8 years 12 13 14 15 18 19 28 38 39 40 41 42 43 45 46 48 .…”
Section: Prognostic Value Of Coronary Calcium Scorementioning
confidence: 99%
See 1 more Smart Citation
“…MACE rates in stable chest pain patients with CCS 0 were reported in 19 studies ( Supplementary Table 3 ). CCS 0 was present in 27–100 % of the included cohorts 12 13 14 15 18 19 28 38 39 40 41 42 43 44 45 46 47 48 . Of the CCS 0 patients, 0–2.1 % suffered from MACE during a follow-up period from 1.6 to 6.8 years 12 13 14 15 18 19 28 38 39 40 41 42 43 45 46 48 .…”
Section: Prognostic Value Of Coronary Calcium Scorementioning
confidence: 99%
“…21 studies reported the event rate of MACE in patients with CCS > 0 ( Supplementary Table 4 ) 12 13 14 15 18 19 28 38 39 40 41 42 43 44 45 46 47 . Event rates ranged from 0.6 % to 34 % during a follow-up of 1 to 6.8 years 12 13 14 15 18 19 21 28 37 38 39 40 42 43 45 46 .…”
Section: Prognostic Value Of Coronary Calcium Scorementioning
confidence: 99%